Perinatal and early-life cobalt exposure impairs essential metal metabolism in immature ICR mice. (March 2021) - Skalny, Anatoly V.; Gluhcheva, Yordanka; Ajsuvakova, Olga P.; Pavlova, Ekaterina; Petrova, Emilia; Rashev, Pavel; Vladov, Ivelin; Shakieva, Roza A.; Aschner, Michael; Tinkov, Alexey A.
Abstract: The objective of the present study was to assess the impact of cobalt (Co) exposure on tissue distribution of iron (Fe), copper (Cu), manganese (Mn), and zinc (Zn), as well as serum hepcidin levels in immature mice (18, 25, 30 days). Pregnant mice were exposed to 75 mg/kg b.w. cobalt chloride (CoCl2  × 6H2O) with drinking water starting from 3 days before delivery and during lactation. At weaning (day 25) the offspring were separated and housed in individual cages with subsequent exposure to 75 mg/kg b.w. CoCl2 until 30 days postnatally. Evaluation of tissue metal levels was performed by an inductively coupled plasma-mass spectrometry (ICP-MS). Serum hepcidin level was assayed by enzyme linked immunosorbent assay (ELISA). Cobalt exposure resulted in a time- and tissue-dependent increase in Co levels in kidney, spleen, liver, muscle, erythrocytes, and serum on days 18, 25, and 30. In parallel with increasing Co levels, CoCl2 exposure resulted in a significant accumulation of Cu, Fe, Mn, and Zn in the studied tissues, with the effect being most pronounced in 25-day-old mice. Cobalt exposure significantly increased serum hepcidin levels only in day18 mice. The obtained data demonstrate that Co exposure may alter essential metal metabolism in vivo . Graphical abstract: Image 1 Highlights: The effects of Co on metal levels were studied in 18, 25, and 30-day old mice. Co exposure resulted in a time- and tissue-dependent increase in Co levels. Co exposure resulted in co-accumulation of Cu, Fe, Mn, and Zn in the studied tissues. Co exposure significantly impacted hepcidin levels only in day18 mice. Alterations in metal homeostasis may be considered a mechanism of Co-induced toxicity.